Penerapan Program Makanan Tambahan (PMT) Berbasis Bahan Pangan Lokal untuk Meningkatkan Asupan Nutrisi - Christina Anugrahini; Maria Fatimah W.A Fouk; Sefrina Maria Seuk Asa; Maria Julieta Esperanca Naibili; Pius A.L Berek (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Background: Nutrition is a problem in toddlers and remains a major issue in efforts to improve the quality of public health in Indonesia. Objective: Implement a supplementary food program (PMT) based on local food ingredients to improve the nutritional intake of toddlers. Implementation method: Target identification and selection, namely by conducting an initial survey of toddlers’ nutritional status through posyandu data and measuring weight and height. Local food processing training, namely by training cadres and mothers of toddlers on how to process local food ingredients into healthy supplementary food programs. Providing supplementary food programs every day for 30 consecutive days, with a varied menu based on local food. Monitoring and evaluation, namely by monitoring body weight and height, is carried out after 30 days of providing the supplementary food program. The provision of supplementary food programs is monitored every day. Results: The level of knowledge of mothers regarding supplementary food programs based on local food ingredients to improve the nutritional intake of toddlers increased on average from 63.4 to 88. Body weight before and after the implementation of the supplementary food program based on local food ingredients increased on average by 0.1 kg. Height before and after the implementation of the supplementary food program based on local food ingredients increased on average by 0.3 cm. Conclusion: The formation of a local food-based PMT implementation team involving a supplementary food program team consisting of cadres, village officials, and nurses. Increased maternal knowledge regarding the implementation of local food-based PMT. Improved nutritional intake in toddlers in terms of weight and height before and after the implementation of the local food-based PMT program.